Approach Paper to the Ninth Five Year Plan (1997-2002) - Planning Commission, Government of India (Planning Commission, Government of India, 1997)
The Ninth Plan will be launched in the 50th year of the independence of our country. This is an opportune moment to take stock of the success of our planning process as well as its failures, and to provide appropriate direction for the socio-economic development of the country. The principal task of the Ninth Plan will be to usher in a new era of people-oriented planning, in which not only the Governments at the Centre and the States, but the people at large, particularly the poor, can fully participate. A participatory planning process is an essential precondition for ensuring equity as well as accelerating the rate of growth of the economy.
Meeting of the National Development Council
Government of India Planning Commission
Keywords: Ninth Five Year Plan- NDC